Pengembangan Vidio Pembelajaran Berbasis Aplikasi CapCut Pada Materi Sistem Pernapasan Manusia - Fanny, Vio; Harahap, Risma Delima; Hasibuan, Rosmidah (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to develop a learning video based on the CapCut application which contains material explaining the respiratory system in humans equipped with sound and images. This research is the development of the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation). The ADDIE model includes five stages, however, in this research only three stages were applied, namely analysis, design and development. This research was carried out at SMP Negeri 1 Pangkatan. The subjects of this research were media experts, material experts in the field of biology, and students in class VII5 of SMP Negri 1 Pangkatan. This type of research data is qualitative data and quantitative data. Validation was carried out by media experts and material experts in the field of biology. The validation results show that the learning video is classified as "Very Eligible" with an appropriateness percentage of 90.5% by media experts and 89.6% by material experts, respectively. Student responses were also very positive with an average score of 4.31. This learning video is considered effective in increasing students' understanding of the human respiratory system material and can be used as supporting media in the learning process.